Post-transcriptional Regulation of HTLV Gene Expression: Rex to the Rescue - D’Agostino, Donna M.; Cavallari, Ilaria; Romanelli, Maria Grazia; Ciminale, Vincenzo (Frontiers in Microbiology, 2019)
Human T-lymphotropic virus type 1 (HTLV-1) and other members of the Deltaretrovirus genus code for a regulatory protein named Rex that binds to the Rex-responsive element present on viral mRNAs. Rex rescues viral mRNAs from complete splicing or degradation and guides them to the cytoplasm for translation. The activity of Rex is essential for expression of viral transcripts coding for the virion components and thus represents a potential target for virus eradication. We present an overview of the functional properties of the HTLV-1 and HTLV-2 Rex proteins (Rex-1 and Rex-2), outline mechanisms controlling Rex function, and discuss similarities and differences in the sequences of Rex coded by HTLV-1, -2, -3 and -4 that may influence their molecular anatomy and functional properties.